About the possibility of protecting UAVs from suppression of control signals - Mytsenko, I.M.; Pedenko, Yu.A.; Roenko, A.N. (Radiotekhnika, 2024)
Unmanned aerial vehicles (UAVs) are widely used in a wide variety of sectors, both in the national economy and for military purposes. In the agricultural industry, they are used to monitor farmland, analyze soil samples, and even for livestock grazing. In search and rescue operations, UAVs are used to rescue people from life-threatening situations, and each time this technology proves its usefulness more than ever. UAVs are gradually finding their application in retail trade, transportation, entertainment, home security and even in construction using 3D printers. Simultaneously with the growth of the capabilities of UAVs, methods and means were developed to counteract them. The most affordable method of combating an UAV is to suppress the radio signals used to control it. As a result, the UAV loses contact with the operator, which leads to malfunctions in its operation. Therefore, the relevance of developing methods and means of combating suppression of control signals cannot be doubted and is becoming more and more necessary. The purpose of the work is to develop a scheme of the device (protection unit) that protects the UAV from interference radio signals in the operating mode. The peculiarity of the developed device is that in the absence of interference signals on the standard frequency of the UAV, the protection unit receives the operator’s control signal and transmits it to the input of the UAV receiver, which moves in the operating mode and performs the tasks assigned to it. In the event of the appearance of interference radio signals on the standard frequency, it independently detects them and, using the UAV transmitter, issues a command to the operator to change the operating frequency to an additional frequency. At the same time, the output frequency of the protection unit remains constant and is equal to the standard frequency of the UAV. Thus, the protection unit is a simple and inexpensive device that detects interference signals and automatically switches the control of the UAV to an additional operating frequency. A functional diagram of the receiving device was developed, and a detailed description of its operation was provided.